Mechanism Design and System Control for Humanoid Space Robot Movement Using a Simple Gravity-Compensation System. (15th November 2013) - Jiang, Zhihong; Liu, Shilong; Li, Hui; Dong, Que; Chen, Xiaopeng; Huang, Qiang
Space robots are an effective resource for astronauts working in a dangerous space environment. This paper proposes and implements a system to validate the performance of robot movement in space. A humanoid robot was designed with a vision-based self-calibration and navigation system. In addition, a path planning method was proposed to minimize joint torque. Simple gravity-compensation equipment with active and passive mechanisms was proposed. However, the flexible connection required for free movement between the robot and the gravity-compensation equipment meant that the space robot was likely to vibrate when moving. In order to address this challenge, a new hybrid force-position controller with joint torque feedforward was proposed. This controller was based on the system dynamics model with a particular focus on joint dynamics. Experimental test results validated the system design and methodology, showing that the humanoid space robot could move sufficiently using simple gravity-compensation equipment.